al-Manhaj al-Dirasi wal Ithar al-Mafahimi Li i’dad Muallimi al-Lughah al-Arabiyah fi Jamiah Maulana Malik Ibrahim al-Islamiyah al-Khukumiyah Malang - Mutholib, Abdul; Retnanto, Agus (Dinamika Ilmu, 2020)
This research aims to describe the reality of the curriculum of teacher preparation in the Department of Arabic Language Teaching at the Maulana Malik Ibrahim Islamic State University Malang and unveiling the conceptual framework for the preparation of Arabic language teachers in this Department.  The methodology used in this paper is the qualitative case study. The results of this research are that the curriculum for the preparation of teachers in the Department of Arabic Language Teaching at this university is based on competencies based curriculum  and the criterion of the Indonesian national framework for qualifications and the idea of the education of the first kernel, which includes the development of personality and the aspect of pedagogy and research and Arabic language science, to provide students with teaching skills and competencies in the field; and The conceptual framework for the preparation of teachers in this department includes the philosophy and standards of the department, the vision, mission and objectives, the included cognitive rules, specifications for graduates, and the system of evaluation adopted for it. The theoretical conclusion of this research is that the quality of the curriculum for the preparation of teachers depends on the extent of the link between the teacher preparation program and its conceptual framework, and the potential of the institutions of preparation to equip students to translate educational theories into practical teaching in schools.